Adidas acquires Under Armour : a new era in Sporting Goods - Nunes, Vítor Hugo Silva (2018)
What would happen to the Sporting Goods Industry if the largest sportswear manufacturer in Europe and second largest in the world decided to buy one of the fastest growing companies, with a very strong presence in the USA? The aim for this dissertation is to correctly evaluate the pricing for both Adidas AG and Under Armour, Inc., in a deal that would strengthen the German company. The objective is simple: dominate the largest market in the world, North America, and dethrone the giant Nike. This dissertation will center on valuing both companies, with a focus on the combined synergies resulting from the merger. For that, I computed three valuation methods: Discounted Cash-Flow (DCF), Adjusted Present Value (APV), and Relative Valuation (Multiples). I will also provide an industry and company overview, in order to extract the main conclusions, and its impact on a worldwide level. In the end, my recommendation is that Adidas acquires Under Armour with a premium of 34% over each share class, as follows: Class A valued at €17,97, Class C valued at €15,62 and Class B, not publicly traded, at €39,12. This will result in a total value of €8.139 million, €2.067 million over the Market Capitalization.